Level of involvement of shea butter processors in processing activities in North-central, Nigeria (2019)
The study examined the level of involvement of Shea butter processors in processing activities in North-central Zone of Nigeria. A multistage sampling procedure was used to select 330 respondents for the study. The data was collected through an Interview schedule and analysed with descriptive and inferential statistics. The result of the findings shows that the average age of the respondents was 40.2 years, with 97.9% and 97.0% being female and of Islamic faith respectively. They have average household size of 8.78 persons and 54.8% were members of cooperative with an average working experience of 19.40 years. Generally, the respondents had low level of involvement in Shea butter processing activities (57.9%), though there was high level of involvement in milling of the nuts (1.69) and boiling dough (1.667). The respondents were able to meet their basic needs of life through their involvement in Shea butter processing activities. However, lack of credit facilities and high cost of processing equipment were the major constraints to Shea butter processing. There were significant relationship between memberships of Shea butter processors (χ²= 20.8, p=0.00), age (r=0.17, p=0.03), years of experience (r=0.21, p=0.00), benefit (r=0.44, p=0.00) and constraints (r=0.23, p=0.00) with their level of involvement in Shea butter processing. There is the need to sensitise the processors on the benefits inherent in Shea butter production and belonging to Shea butter processors association to increase the level of involvement and income generation for the processors.